Dialectics of Debate: Reflections on Three Pedagogical Scenes in Chinese Music History - S. K. Lee, Gavin (Current Musicology, 2019)
Abraham Maslow’s theory of the hierarchy of needs with self-actualization at the pinnacle has been influential in educational philosophy, but pedagogy solely in this Western liberal sense does not fully account for delimited global contexts in which pedagogy may at certain times equate indoctrination, as when Chinese students are taught about the supremacy of the Communist Party of China. In this latter context, what applies is a different form of “pedagogy,” defined and critiqued by postcolonial theorist Homi Bhabha as the propagation of the ideology of a homogeneous nation void of the heterogeneity of differences. Through my deployment of various teaching materials related to Chinese music history, I demonstrate how the discursive space in my classroom can embody Bhabha’s central theory of ambivalence, as nationalist pedagogy is countered by students’s performative acts of self-actualization. Rather than regarding heterogeneity as an ethical anchor to be preferred over homogeneity, however, I end this essay by arguing that what we need is a dialectical pedagogy of both heterogeneity and homogeneity. Dialectics begins with a simple classroom debate.